Creep and relaxation of nonlinear viscoelastic materials, with an introduction to linear viscoelasticity - Findley, William N. (William Nichols); Lai, James S.; Onaran, Kasif (North-Holland series in applied mathematics and mechanics, 1976)
Creep And Relaxation Of Nonlinear Viscoelastic Materials With An Introduction To Linear Viscoelasticity.